BOOKSELLERS, PUBLISHERS AND PRESS WORKERS IN THE SECOND HALF OF THE 19TH AND EARLY IN THE 20TH CENTURY IN ESTONIA - JANTSON, SIGNE (Knygotyra, 2015)
The article handles general developments and changes in book trade and book publishing which took place in Estonia during the second half of the 19th and in the early 20th century. The aim is to show the formation of bookshops trading with Estonian books, to analyse the activities of Estonian booksellers as publishers and their role in publishing books in the Estonian language. The paper is based on the retrospective national bibliography of Estonian books that were published from 1850 to 1917, on research literature and on the data collected by the author for her doctoral thesis.
Keywords: history; 19th century; Estonia; book trade; publishing; booksellers as publishers